A bacterial artificial chromosome-based framework contig map of human chromosome 22q. - Kim, U J (1996)
We have constructed a physical map of human chromosome 22q using bacterial artificial chromosome (BAC) clones. The map consists of 613 chromosome 22-specific BAC clones that have been localized and assembled into contigs using 452 landmarks, 346 of which were previously ordered and mapped to specific regions of the q arm of the chromosome by means of chromosome 22-specific yeast artificial chromosome clones. The BAC-based map provides immediate access to clones that are stable and convenient for direct genome analysis. The approach to rapidly developing marker-specific BAC contigs is relatively straightforward and can be extended to generate scaffold BAC contig maps of the rest of the chromosomes. These contigs will provide substrates for sequencing the entire human genome. We discuss how to efficiently close contig gaps using the end sequences of BAC clone inserts.